2014
DOI: 10.1074/jbc.m114.567743
|View full text |Cite|
|
Sign up to set email alerts
|

TNF-TNFR2/p75 Signaling Inhibits Early and Increases Delayed Nontargeted Effects in Bone Marrow-derived Endothelial Progenitor Cells

Abstract: Background: Ionizing radiation can induce DNA damage in nonirradiated (N-IR) cells via nontargeted effects (NTE). Results: TNF-␣ and IL-1␣ mediate NTE in N-IR bone marrow-derived EPCs, and neutralizing TNF-␣ diminishes NTE in WT and p55 knock-out BM-EPCs. Conclusion: TNF-TNFR2/p75 signaling alters accumulation of inflammatory cytokines that attenuate NTE in N-IR EPCs. Significance: TNFR2/p75 may represent a gene target for mitigation of delayed RBR in BM-EPCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 93 publications
3
15
0
Order By: Relevance
“…The activation of the TNFR signaling pathway, one of the apoptosis p53 independent pathways, has also been shown highly radiation responsive in many tissues and cells (53). Consistent with the fact that inflammatory processes are involved in the initial events triggering atherosclerotic development after radiation exposure, we observed that inflammation associated pathways (NF-kB and Toll like receptor pathways) are sensitive to proton and gamma radiation exposure in a dosage-dependent manner (54).…”
Section: Discussionsupporting
confidence: 80%
“…The activation of the TNFR signaling pathway, one of the apoptosis p53 independent pathways, has also been shown highly radiation responsive in many tissues and cells (53). Consistent with the fact that inflammatory processes are involved in the initial events triggering atherosclerotic development after radiation exposure, we observed that inflammation associated pathways (NF-kB and Toll like receptor pathways) are sensitive to proton and gamma radiation exposure in a dosage-dependent manner (54).…”
Section: Discussionsupporting
confidence: 80%
“…that trigger inflammation and other cellular effects. [14][15][16] IL-10 has been identified as an immunosuppressive and anti-inflammatory cytokine secreted by monocytes, Th 2 cells, B cells, mast cells, dendritic and regulatory T cells, etc. [17][18][19] Upon irradiation, IL-10 expression has been found to be amplified, which affects antigen presentation capacity of APCs, resulting in inhibition of Th 1 cells activation in irradiated cells 20 resulting in immunosuppression.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms underlying RIBE have been one of the hot topics in radiation biology since 1992, when Nagasawa et al, demonstrated the phenomenon of RIBE [1]. RIBE are the consequences of intercellular communication by nature, which can be mediated through intercellular gap junctions [5], reactive oxygen species (ROS) / nitric oxide (NO) [20][21][22] and soluble signaling molecules such as cytokines [23]. For example, interleukin-6, 8, 33 and tumor growth factor β1 (TGF-β1) have been found to be one of the RIBE mediators [2,24].…”
Section: Discussionmentioning
confidence: 99%